Team Coping: Cross-Level Influence of Team Member Coping Activities on Individual Burnout - Kamphuis, Wim; Delahaij, Roos; de Vries, Thomas A. (Frontiers in Psychology, 2021)
Coping with stress has been primarily investigated as an individual-level phenomenon. In work settings, however, an individual’s exposure to demands is often shared with co-workers, and the process of dealing with these demands takes place in the interaction with them. Coping, therefore, may be conceptualized as a multilevel construct. This paper introduces the team coping concept and shows that including coping as a higher-level team property may help explain individual-level outcomes. Specifically, we investigated the effects of exposure to danger during deployment on burnout symptoms in military service members, and examined to what extent this relationship was moderated by individual-level and team-level functional coping. We hypothesized that the relationship between individuals’ exposure to danger and burnout is contingent on both. In line with our predictions, we found that service members who were highly exposed to danger, and did not engage in much functional coping, suffered most from burnout symptoms, but only when their teammates did not engage in much functional coping either. When their teammates did engage in much functional coping, the effect of exposure to danger on burnout was buffered. Hence, team members’ coping efforts functioned as a resilience resource for these service members.